A global standard for monitoring coastal wetland vulnerability to accelerated sea-level rise - Webb, E.L; Friess, D.A.; Krauss, K.W.; Cahoon, D.R; Guntenspergen, G.R; Phelps, J. (Springer, 2013)
Reliable measurements of changes in wetland surface elevation are necessary to understand and predict the probable impact of sea-level rise on vulnerable coastal ecosystems and for science-informed management, adaptation and mitigation. A simple, inexpensive and low-technology device called the 'rod surface elevation table' could be used to monitor threatened coastal wetlands around the world. Sea-level rise threatens coastal salt-marshes and mangrove forests around the world, and a key determinant of coastal wetland vulnerability is whether its surface elevation can keep pace with rising sea level. Globally, a large data gap exists because wetland surface and shallow subsurface processes remain unaccounted for by traditional vulnerability assessments using tide gauges. Moreover, those processes vary substantially across wetlands, so modelling platforms require relevant local data. The low-cost, simple, high-precision rod surface-elevation table–marker horizon (RSET-MH) method fills this critical data gap, can be paired with spatial data sets and modelling and is financially and technically accessible to every country with coastal wetlands. Yet, RSET deployment has been limited to a few regions and purposes. A coordinated expansion of monitoring efforts, including development of regional networks that could support data sharing and collaboration, is crucial to adequately inform coastal climate change adaptation policy at several scales.